2009
DOI: 10.1103/physrevlett.103.096104
|View full text |Cite
|
Sign up to set email alerts
|

Atom-By-Atom Quantum State Control in Adatom Chains on a Semiconductor

Abstract: The vertical manipulation of native adatoms on a III-V semiconductor surface was achieved in a scanning tunneling microscope at 5 K. Reversible repositioning of individual In atoms on InAs(111)A allows us to construct one-atom-wide In chains. Tunneling spectroscopy reveals that these chains host quantum states deriving from an adatom-induced electronic state and substantial substrate-mediated coupling. Our results show that the combined approach of atom manipulation and local spectroscopy is capable to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 29 publications
2
47
0
1
Order By: Relevance
“…[21]). In adatoms (either native or artificially created by soft tip indentation) can be readily repositioned by the STM tip 21,32 . Due to the low screening provided by the semiconductor surface, the In adatom charge is strongly localized and by repositioning and arranging them we can tailor the local electrostatic potential.…”
Section: Resultsmentioning
confidence: 99%
“…[21]). In adatoms (either native or artificially created by soft tip indentation) can be readily repositioned by the STM tip 21,32 . Due to the low screening provided by the semiconductor surface, the In adatom charge is strongly localized and by repositioning and arranging them we can tailor the local electrostatic potential.…”
Section: Resultsmentioning
confidence: 99%
“…By mapping the local electrostatic potential [22], we found that the In ad donor character is consistent with a charge state +1 [17]. In addition, In ad atoms are weakly bound to the surface and can be repositioned by the STM tip [18,23]. The STM topography image in Fig.…”
mentioning
confidence: 92%
“…The InAs(111)A surface exhibits features significantly different from those of GaAs(110): a reduced bandgap of 0.42 eV and Fermi-level pinning in the conduction band due to the presence of surface-accumulated electrons, 37,38 preventing TIBB. On the other hand, a feature in common is that InAs(111)A is characterized by completely saturated dangling bonds due to its intrinsic ð2 Â 2Þ In-vacancy reconstruction, 39 rendering the surface chemically nonreactive.…”
Section: B Npc On Inas(111)amentioning
confidence: 99%